Rekiske: Interdisciplinary platform for sharing knowledge and experience of Japanese historical documents. Issue 1 (14th February 2022) - Ichino, Mika; Masuda, Kooiti
Abstract: Historical materials contain descriptions of various events involved in natural processes and human societies (such as weather, earthquakes, volcanic eruptions, harvests, market prices, and famines). They have been used for studies in diverse fields, including natural sciences (such as seismology, climatology, and astronomy), social sciences, and humanities. Hence, researchers have made various efforts, such as identifying and obtaining the materials, reading handwritten characters and transcribing them into digital texts, standardizing formats, extracting descriptions of relevant phenomena, and constructing integrated datasets, to use documentary information. Because scientists, other than historians, find it quite challenging even to ascertain where to find appropriate research materials, the Rekiske Development Group has, therefore, developed a system called Rekiske to facilitate interdisciplinary sharing of information available from historical materials. Rekiske is designed for sharing bibliographic and scientific information of historical materials, along with researchers' experience and knowledge, through interdisciplinary collaboration. Rekiske can assist researchers in identifying and obtaining useful historical materials for research purposes. It also facilitates collaboration among experts to share their expertise and knowledge of historical information, materials, and recent studies. Using Rekiske, we register various types of information on historical materials regarding weather or earthquakes considered in geoscience research to utilize researchers' experiences and to produce new knowledge through interdisciplinary collaborations. The developed system is designed to be used as a metadata portal and pathfinder to promote and preserve historical data and facilitate an understanding of the spatiotemporal connection between nature and human society. We have applied Rekiske to historical climatic studies and discuss its usage, benefits, usability, and other remaining issues. Abstract : Rekiske is a system designed for sharing bibliographic and scientific information on historical materials, along with researchers' experience and knowledge, through interdisciplinary collaboration. It is expected to assist researchers working with historical documents and contribute to preserving historical materials. Case studies of historical climatology are introduced. The diagram below shows recording periods of diaries with daily weather descriptions.